Experimental Analysis of Metal Composites - Prasad Tripathy, Hara; Pattanaik, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2025)
Herein, in this process there was an attempt to prepare aluminum alloy metal matrix composite to examine its machinability, mechanical properties & physical properties. Discovery tells that, alloy of aluminum material is the best alternative for designing the material to give the essential characteristics. Alloy of aluminum metal matrix composite is getting vital recognition for using in vehicle and airplane, because of its low density, higher strength, high degree of stiffness & more resistance towards rusting. The AA7075 aluminum alloy is prepared by reinforcing the TiB2 (titanium borate), this composite is developed by applying TiB2 in the alloy of aluminum AA7075 according to mass ratio 5%, 10%, 15% respectively. The composite is formed with stir casting techniques. Furthermore, there are a wide variability of mechanical & physical tests are done such as hardness test, tensile test and microstructure testing. A hardness testing is conducting by using the Rockwell hardness test instrument. This test shows that addition to the reinforcement of TiB2 is increases its value of hardness, however an intensification in reinforcement nearly to 15%. The proliferation in reinforcement will decrease the hardness value.